Antimetabolic cooperativity with the clinically approved l-asparaginase and tyrosine kinase inhibitors to eradicate CML stem cells - Anne Trinh; Raeeka Khamari; Quentin Fovez; François-Xavier Mahon; Béatrice Turcq; Didier Bouscary; Patrice Maboudou; Marie Joncquel; Valérie Coiteux; Nicolas Germain; William Laine; Salim Dekiouk; et al. (Elsevier, 2022)
Objective: Long-term treatment with tyrosine kinase inhibitors (TKI) represents an effective cure for chronic myeloid leukemia (CML) patients and discontinuation of TKI therapy is now proposed to patient with deep molecular responses. However, evidence demonstrating that TKI are unable to fully eradicate dormant leukemic stem cells (LSC) indicate that new therapeutic strategies are needed to control LSC and to prevent relapse. In this study we investigated the metabolic pathways responsible for CML surviving to imatinib exposure and its potential therapeutic utility to improve the efficacy of TKI against stem-like CML cells. Methods: Using complementary cell-based techniques, metabolism was characterized in a large panel of BCR-ABL+ cell lines as well as primary CD34+ stem-like cells from CML patients exposed to TKI and L-Asparaginases. Colony forming cell (CFC) assay and flow cytometry were used to identify CML progenitor and stem like-cells. Preclinical models of leukemia dormancy were used to test the effect of treatments. Results: Although TKI suppressed glycolysis, compensatory glutamine-dependent mitochondrial oxidation supported ATP synthesis and CML cell survival. Glutamine metabolism was inhibited by L-asparaginases such as Kidrolase or Erwinase without inducing predominant CML cell death. However, clinically relevant concentrations of TKI render CML cells susceptible to Kidrolase. The combination of TKI with Lasparaginase reactivates the intinsic apoptotic pathway leading to efficient CML cell death. Conclusion: Targeting glutamine metabolism with the FDA-approved drug, Kidrolase in combination with TKI that suppress glycolysis represents an effective and widely applicable therapeutic strategy for eradicating stem-like CML cells.